PENGARUH PENAMBAHAN EKSTRAK TEH HIJAU TERHADAP TOTAL FENOL DAN SIFAT ORGANOLEPTIK MINUMAN POPPING BOBA TERONG BELANDA - Siska Aldrika (2020)
Diabetes mellitus (DM) can trigger the formation of free radical compounds in the body. Green tea is one of the foods that contain high phenolic content, which is useful for reducing free radical compounds. The purpose of this study is to analyze the effect of green tea extract addition to phenolic content and sensory acceptance of tamarillo popping boba drinks, to choose the best formula, and to know the nutrition content of this product. This study uses an experimental research design with a completely randomized design (CRD) one factor with two repetitions. This product divided into 3 formula of F1 addition 10%, F2 addition 15%, and F3 addition 20% of green tea extract. Organoleptic and phenolic content data were analyze using Kruskall Wallis test and ANOVA respectively. If There's a significant result continued with Mann Whitney test and Duncan test respectively. The result shows that there's significant effect of green tea extract addition to panelist preference on scent parameter (p=0,028), on taste parameter (p=0,019), and on phenolic content (p=0,033) of tamarillo popping boba drink. The selected formula is F3 with green tea ekstrak addition 20% having a water content of (87,834%), ash content (0,469%), protein content (0,083%), fat content (<0,02%), carbohydrate content (10,86%), and phenolic content (81.202 ± 1,598 mg GAE/100g).